1-Ethyl-β-N-acetylglucosaminide increases hyaluronan production in human keratinocytes by being converted to N-acetylglucosamine via β-N-acetylglucosaminidase-dependent manner. Issue 6 (9th April 2021) - Akazawa, Yumiko; Yoshida, Hiroyuki; Endo, Yoko; Sugita, Jun; Yakumaru, Masafumi; Sayo, Tetsuya
ABSTRACT: Regulation of hyaluronan (HA) is important for the maintenance of epidermal homeostasis. Here, we examined the mechanism by which 1-ethyl-β- N -acetylglucosaminide (β-NAG2), a newly developed N -acetylglucosamine (NAG) derivative, increases HA production in cultured human epidermal keratinocytes. When keratinocytes were treated with β-NAG2, mRNA expression of HA synthase 3, which is responsible for HA production in human keratinocytes, was not influenced, but the intracellular level of UDP-NAG, a substrate used for HA synthesis, was increased. By using a synthetic substrate for β- N -acetylglucosaminidase (β-NAGase), keratinocytes were found to possess β-NAGase activity, and treatment of o -(2-acetamido-2-deoxy-d -glucopyranosylidene) amino N -phenyl carbamate (PUGNAc), an inhibitor of β-NAGase, abolished the release of NAG from β-NAG2 in keratinocytes. Furthermore, PUGNAc attenuated the β-NAG2-induced intracellular UDP-NAG and HA production in keratinocytes. These results suggest that β-NAG2 is converted to NAG by endogenous β-NAGase in keratinocytes, and the resulting NAG is further metabolized to UDP-NAG and utilized for HA production. Graphical Abstract: